A STUDY OF STROMAL CD34 AND SMOOTH MUSCLE ACTIN IMMUNOEXPRESSION IN BENIGN AND MALIGNANT BREAST LESIONS AT A TERTIARY CARE CENTER IN NORTHERN INDIA: A CROSS-SECTIONAL STUDY. - Rai, Priyanka; Mitra, Shaila; Kumar, Yogesh; Pandey, Saurabh (Student’s Journal of Health Research Africa, 2024)
Background This study aimed to explore the distribution of CD34 and smooth muscle actin (SMA) positive myofibroblasts within the stroma of different benign and malignant breast lesions. Material and methods A total of 98 individuals with breast specimens acquired by surgery or biopsy were studied histopathologically and immunostained for CD34 and SMA using the avidin-biotin-peroxidase method. Appropriate comparisons among the distribution of CD34 and SMA along with statistical analysis were done to compare the sensitivity and specificity of each marker regarding the identification of benign and breast diseases. Result The histopathological findings included non-proliferative breast diseases (fibroadenoma, fibrocystic disease, phyllodes, gynecomastia, fibroadenosis), proliferative changes with and without atypia, carcinoma in situ, and invasive breast carcinoma. CD34 was positive in 98.27% of benign and negative in 92.37% of malignant breast diseases. SMA was strongly positive in 6.89% of benign and 80% of malignant breast diseases. In both DCIS and invasive breast carcinomas, there was a consistent loss of CD34 expression alongside a rise in SMA positivity. The sensitivity and specificity of CD34 stromal expression were 98.27% and 92.5%, respectively, while for SMA, they were 87.5% and 86.2%, respectively. Conclusion The combined assessment of CD34 and SMA holds promise as a diagnostic tool for recognizing the differences between benign and cancerous breast lesions. However, relying on either marker alone does not yield sufficiently distinct results. Recommendations Future studies should include detailed correlation analysis between CD34 and SMA expressions in breast fibroblasts to provide a more comprehensive understanding of their diagnostic value in distinguishing benign from malignant breast lesions.